The Impact of Oral Health Knowledge, Attitude and Practices (KAP) of Kindergarten Teachers on Their Oral Condition in Al-Rusafa Sector/ Baghdad-Iraq. - Israa S Al-Atiyah; Nada J Radhi (College of Dentistry/ University of Baghdad, 2018)
Background: Teachers are considered as dynamic force who take a pivotal position in any educational system. Since they may play a significant role in passing the preventive information and health promotion, it is important that their own oral health knowledge, attitude, and practices conform to the professional recommendations. The aim of this study was to evaluate oral health knowledge, attitude and practices among kindergarten teachers, and their impact on teachers' oral health condition in Al-Rusafa Sector, Baghdad, Iraq. Materials and Methods: This cross-sectional survey was conducted among 80 kindergarten teachers. A self-administered questionnaire was distributed among these teach¬ers. This questionnaire format contains two parts that deals with oral health knowledge, attitude and practices of teachers, and this was followed by clinical oral examination for all the teachers. Simple random sampling technique was employed for the selection of the study participants. Descriptive analysis was done and data was analyzed using Bonferonni t-test and ANOVA test. Results: Teachers demonstrated adequate but incomplete knowledge regarding oral health. More than 85.0% of teachers were aware of preventive measures to keep good oral health and knew the bad influence of neglecting the oral hygiene. About 65.0% of teachers had the awareness about dental plaque composition and its bad effects. Meanwhile, 45.0% of them were aware about the signs of tooth decay, also 32.5% were aware about the benefits of regular correct brushing on the gingiva. No obvious differences were noticed regarding teachers' DMFS, plaque and gingival indices mean values in association to the level of teachers' knowledge, however, a positive relation were found between favorite attitude and practices and mean values of DMFS, plaque and gingival indices. Conclusions: The studied kindergarten teachers demonstrated adequate but incomplete oral health knowledge with many of them adopting poor attitude and practices. There is a definite and immediate need for an integral educational program for kindergarten teachers on basic oral health knowledge and favorable practices. Moreover, teachers' healthy practices can affect their oral health condition positively.